Characterisation of acrylonitrile styrene acrylate modified asphalt cement with nano iron oxide and nano silica particles - Mustafa Alas,; Kurthan Korutürk, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current study investigated the physical properties and rheological characteristics of asphalt cement (AC) modified by nano ironoxide (Fe3O4) and nano silica (SiO2) particles. Seven different blends including base AC, Acrylete-Styrene-Acrylonitrile (ASA)/ Nanosilica (Si) and ASA/ Nanoironoxide (Fe) were the subject of experimental investigations. ASA was used at 5% for all modified blends while the nanomaterials were blended in 3, 5 and 7% concentrations by the weight of AC. Temperature susceptibility, rotational viscosity (RV) and storage stability for the base and polymer nanocomposite modified asphalt cement (PNCAC) were evaluated by the physical testing procedures while the frequency sweep test and the multiple stress creep recovery (MSCR) tests were conducted using a dynamic shear rheometer. The results showed that, the viscoelastic properties of the ASA/Si and ASA/Fe modified binders were improved when subjected to a range of temperatures and loading conditions. ASA/Fe composite modified AC demonstrated superior high temperature performance characteristics while ASA/Si composite modified AC although presented less significant improvement at the high temperature conditions, it was also able to improve the intermediate temperature fatigue resistance of asphalt more than the ASA/Fe composite modified AC. The optimum concentration of additives were found to be 3 and 5% for the ASA/Fe and ASA/Si modified AC respectively. Further addition of nanomaterials beyond the abovementioned concentrations resulted in degradation of the enhancement in physical and rheological properties of PNCAC, which was associated to the occurrence of agglomeration of nanoparticles and phase separation between the polymer-nanomaterial-asphalt matrix.